Postoperative intra-abdominal infection increases angiogenesis and tumor recurrence after surgical excision of colon cancer in mice - Bohle, Bernhard Richard; Pera, Miguel; Pascual, Marta; Alonso, Sandra; Mayol, Xavier; Salvado, Margarita; Schmidt, Jan; Grande, Luis (Surgery, 2010)
Background - Recent reports have suggested that anastomotic leakage is associated with greater rates of tumor recurrence and cancer-specific mortality after surgery for colorectal cancer. The impact of postoperative intra-abdominal infection on long-term oncologic results, however, is still controversial, and no direct causal relationship has been found between both processes. Our aim was to investigate the influence of postoperative intraabdominal infection on angiogenesis and tumor growth in an animal model of colon cancer. - Methods - Balb/c mice were randomized immediately after injection of 5×106 B51LiM cells into the cecal wall into 2 groups: cecal resection without postoperative infection (group 1), and cecal resection with postoperative intra-abdominal infection (group 2). A total of 18 days after cell injection, cecectomy was performed, and infection was induced in group 2 by intraperitoneal injection of 3×108 colony-forming units of Bacteroides fragilis. On postoperative day 12, the mice were killed. - Results - Comparing group 1 with group 2, tumor recurrence was more frequent in animals with intraabdominal infection (65% vs 100%, respectively; P =.02). VEGF serum levels were greater at the time of sacrifice in the group with infection (11±10 vs 30±23pg/mL; P < .05). Tumor angiogenesis was also increased in the postoperative infection group. The mean (± standard deviation) microvessel density was 16 ±7 versus 28 ±11 vessels per high-power field (P < .05). - Conclusion - We concluded that postoperative intra-abdominal infection increases angiogenesis and tumor recurrence after operative excision of a colon cancer in mice.
Erstmals am 20. September 2009 veröffentlicht
Gesehen am 02.02.2023